Paramedics' experiences of financial medicine practices in the pre-hospital environment. A pilot study - Craig Vincent-Lambert; Richard-Kyle Jackson (AOSIS, 2016)
Background: The term "financial medicine" refers to the delivery of health-related services where the generation of financial gain or "profit" takes precedence over the provision of care that is reflective of evidence-based best practice. The practicing of financial medicine includes over-servicing and overbilling, both of which have led to a sharp rise in the cost of health care and medical insurance in South Africa. For this reason, the practicing of financial medicine has been widely condemned both internationally and locally by the Health Professions Council of South Africa (HPCSA) and allied Professional bodies. Objectives: This qualitative pilot study explored and described the experiences of South African Paramedics with regard to the practicing of financial medicine in the local pre-hospital emergency care environment. Method: A sample of South African Paramedics were interviewed either face-to-face or telephonically. The interviews were audio recorded and transcripts produced. Content analysis was conducted to explore, document and describe the participants' experiences with regard to financial medicine practices in the local pre-hospital environment. Results: It emerged that all of the participants had experienced a number of financial medicine practices and associated unethical conduct. Examples included Over-servicing, Selective Patient Treatment, Fraudulent Billing Practices, Eliciting of kickbacks, incentives or benefits and Deliberate Time Wasting. Conclusion: The results of this study are concerning as the actions of service providers described by the participants constitute gross violations of the ethical and professional guidelines for health care professionals. The authors recommend additional studies be conducted to further explore these findings and to establish the reasons for, and ways of, limiting financial medicine practices in the South African emergency care environment.